Integrating Local Wisdom of Pesantren into Physics Education: A Torque-Based Analysis of Daily Activities - Aulia, Nurul; Budiyono, Agus; Andi, Herman Jufri; Wildani, Arin (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2024)
This study explored the integration of torque concepts into the local wisdom of Islamic boarding schools (pesantren), emphasizing the application of these principles in everyday activities. The research aimed to connect abstract physics concepts with culturally relevant practices to enhance physics education. Using a descriptive qualitative method, field observations were conducted on 17 pesantren activities, with data collected from 10 students in Pamekasan. Direct observation and photography documented movements related to torque, such as during prayer, ablution, and other daily tasks. The findings identified 29 torque-related movements, including actions like performing ablution and making adzan. These traditional practices were analyzed for their application of force, pivot points, and lever arms, demonstrating their alignment with the concept of torque in physics. The study concluded that integrating these cultural activities into physics education not only aids in understanding theoretical concepts but also enriches the learning experience by incorporating students' cultural backgrounds. This approach promotes a more meaningful and engaging physics education while respecting the cultural values of pesantren students.